The risk of respiratory failure for chronic thromboembolic pulmonary hypertension patients after pulmonary endarterectomy - Szatkowski, Piotr; Dyk, Wojciech; Zygier, Marcin; Sitkowska-Rysiak, Ewa; Wieteska, Maria; Torbicki, Adam; Biederman, Andrzej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Background : Chronic thromboembolic pulmonary hypertension (CTEPH) has poor long term prognosis [1, 2]. Pulmonary endarterectomy (PEA) is a treatment of choice for patients with proximal location of thrombotic material [3]. Aim : Evaluation of post-PEA complication and its risk factors with special reference to development of respiratory failure (RF). Materials and methods : Records of 115 CTEPH patients, 80 males with a mean age of 53 ±13 (25-77) years, operated from October 1995 to April 2010 were reviewed. The patients were divided into two groups: group I without RF and group II with post-PEA RF. Hemodynamic data, procedural data and postoperative course were analysed. Results : Respiratory failure occurred in 32 (28%) of the operated patients. The causes of RF were reperfusion pulmonary oedema (RPO) 26 (22,6%), persistent pulmonary hypertension (PPH) 11 (9,6%), airways bleeding 3 (2,6%). Seven patients died (6,1%). The patients with post-PEA RF (group II) were older (57 ±12 vs. 52 ±14; p = 0,0344) and had significantly higher mean pulmonary arterial pressure (PAP; 54 ±10 vs. 47 ±11 mm Hg; p = 0.0055) and preoperative pulmonary vascular resistance (PVR; 1015 vs. 584 dyn × s × cm –5 ; p = 0.0020) and also longer extracorporeal circulation (ECC; 189 ±62 vs. 161 ±34 min, p = 0.0187) and cardiac arrest (CA; 43 ±17 vs. 32 ±16 min; p = 0.017). Conclusion : Respiratory failure is a frequent complication after PEA. High PVR and PAP before PEA are risk factors of RF and death. RF occurs more frequently after PEA in elderly patients and in those with longer ECC and CA.